DESIGNING INTERACTIVE LEARNING MEDIA FOR WRITING SKILL BY USING MACROMEDIA FLASH 8 - Maysarag Pulungan; Rahmad Husein; Nora Ronita Dewi (Universitas Negeri Medan, 2017)
The aim of this study are: 1) to design interactive learning media for writing skill by using Macromedia Flash 8, and 2) to investigate the eligibility product of interactive for writing skill by using Macromedia Flash 8. Research and development is used as the research method. This research took place at MAN 2 Model Medan. The product has validated by expert validations (material and media). The instrument for collecting data by using questionnaires with Likert scale 1-4. The data was analyzed based on expert validation to revise the product. The result shows that: 1) the material in interactive learning media for writing skill with the average 3.9 (Very eligible, no need revision), and 2) the interactive learning media is eligible, no need revision with average 3.2. Therefore, the product of interactive learning media is appropriate to use as interactive learning media in teaching learning English process. Keywords: Interactive Learning Media, Writing Skill, Macromedia Flash 8